Comparative proteomics of milk fat globule membrane in goat colostrum and mature milk. (15th October 2016) - Lu, Jing; Liu, Lu; Pang, Xiaoyang; Zhang, Shuwen; Jia, Zhenhu; Ma, Changlu; Zhao, Lili; Lv, Jiaping
Highlights: Acute phase response proteins were higher in abundance in goat colostrum milk fat globule membrane. Milk synthesis and secretion proteins were conserved through lactation. Long term depression proteins were present both in colostrum and mature goat milk. Abstract: As an important nutrient source in large area of world, the composition and nutritional value of goat milk are not well deliberated. Detailed annotation of protein composition is essential to address the physiological and nutritional value of goat milk. In the present study, 423 colostrum and mature goat milk fat globule membrane (MFGM) proteins were identified. The abundance of 189 proteins was significantly different between colostrums and mature milk MFGM. The acute phase proteins were higher in colostrums MFGM than those in mature milk MFGM which protected newborns at the beginning of life. Proteins related to synthesis and secretion were conserved through lactation to ensure the milk production. Of note, long term depression (LTD) proteins were observed in colostrum and mature milk MFGM. Milk LTD proteins could be potential biomarkers for diagnosis of lactation related depressive syndromes and should be taken into considerations of their effects on newborns.